2020
DOI: 10.1002/npr2.12147
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of heroin detoxification with buprenorphine in a psychiatric hospital in Japan

Abstract: Heroin is a highly addictive drug produced from morphine, which is a principal component of opium. In addition to its powerful euphoria, heroin induces both psychological and physical dependence, and thus, it is one of the most commonly used illicit drugs worldwide. In the United States, since the 1990s, the widespread use of opioids for noncancer pain has led to a vicious cycle of abuse and resale of these drugs, as well as the abuse of heroin, which can be obtained cheaply, leading to an opioid epidemic 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A study examined the outcomes of buprenorphine substitution therapy for heroin-dependent patients who voluntarily sought treatment at a Japanese psychiatric hospital and found that buprenorphine maintenance therapy significantly reduced withdrawal symptoms during detoxification and improved treatment completion rates. Therefore, the study urges the Japanese government to consider integrating buprenorphine maintenance therapy and existing community-based treatment (Nagano et al, 2020).…”
Section: Drug Policies In the United States East Asia And Taiwanmentioning
confidence: 99%
“…A study examined the outcomes of buprenorphine substitution therapy for heroin-dependent patients who voluntarily sought treatment at a Japanese psychiatric hospital and found that buprenorphine maintenance therapy significantly reduced withdrawal symptoms during detoxification and improved treatment completion rates. Therefore, the study urges the Japanese government to consider integrating buprenorphine maintenance therapy and existing community-based treatment (Nagano et al, 2020).…”
Section: Drug Policies In the United States East Asia And Taiwanmentioning
confidence: 99%